2016
DOI: 10.18869/acadpub.jhs.4.4.41
|View full text |Cite
|
Sign up to set email alerts
|

Removing Fe, Zn and Mn from steel making plant wastewater using RO and NF membranes

Abstract: Background and purpose: Excessive amount of heavy metals in industrial wastewater is a seriously crucial issue and requires efficient methods to be introduced and dealt with. Meanwhile, steel making plants as productive units in every country release large amounts of fluid into surface and underground sources. Typically, this wastewater contains heavy metals in minor amounts, while this amount could cause severe damages to the living organisms. Materials and methods: In this study, removing iron, manganese, zi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Higher rejection rates were found at pH levels equal to 4 or above 6, with low Cd concenterations in the feedwater. Mirbagheri et al (2016) [13] also employed RO membranes to separate Fe, Zn, and Mn from steel industry wastewater at different pHs and feed pressures. They indicated that a high quantity of Fe, Zn, and Mn in industrial wastewater was effectively removed using RO membranes when the pH and pressure were optimized.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Higher rejection rates were found at pH levels equal to 4 or above 6, with low Cd concenterations in the feedwater. Mirbagheri et al (2016) [13] also employed RO membranes to separate Fe, Zn, and Mn from steel industry wastewater at different pHs and feed pressures. They indicated that a high quantity of Fe, Zn, and Mn in industrial wastewater was effectively removed using RO membranes when the pH and pressure were optimized.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have been focusing on the RO method as one of the most promising ways to treat water in recent years. Recent studies have focused on the removal of heavy metals from contaminated water using RO membrane technology [9–13] . For instance, Kheriji et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation